Intelligent, biomimetic, color-tunable, light-emitting artificial skin with memory function. (December 2021) - Zhu, Yangbin; Liu, Yang; Hu, Hailong; Xu, Zhongwei; Wu, Chaoxing; Kim, Dae Hun; Guo, Tailiang; Li, Fushan; Kim, Tae Whan
Abstract: The ability to combine the color-tunability capability of natural organisms with a memory function in a single device is highly desired and holds promise for potential applications such as intelligent artificial skin and human-machine interfaces. In this work, we propose a universal strategy to realize color-tunable skin with the compound function of memory by ingeniously integrating a memristor interface into a flexible quantum-dot light-emitting device. The devices developed using this strategy have multiple responses to electrical and light stimulations and can easily change their color over a wide range from red to green. Moreover, these color-tunable devices can mimic the unique function of "once bitten, twice shy" to enhance self-protection, and their color tunability is consistent with the memory-forgetting curve proposed by psychologists. Graphical Abstract: ga1 Highlights: Artificial intelligent skin has been developed by combining color-tunability and memory into a single light-emitting device. Color-tunable behaviors are correlated so that past light-stimulation experiences can be remembered. The devices have multiple responses to electrical and non-contact light stimulations. The devices can easily change color over a wide range from red to green for better naked-eye perception.